MILITARY EUPHEMISM AS A FORM OF COMMUNICATION: A COMPREHENSIVE ANALYSIS - Alikulov Feruzbek Abdigobborovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article explores the concept of military euphemism as a distinct form of communication, analyzing its functions, forms, and significance in military contexts. By examining the various ways in which euphemisms are employed, this article seeks to illuminate their role in military operations, psychological warfare, diplomacy, and public relations.